The Role of UNHCR in the Stagnation of International Intervention towards Victims of the Coup Conflict in Myanmar as an Effort to Maintain Peace - Ma'arif, Hilman Mahmud Akmal; Maksum, Ali (Global Strategis, 2022)
Myanmar is a country in Southeast Asia with a dire humanitarian crisis that is marked by the existence of conflict and humanitarian issues. The military's arbitrariness against civilians, from ethnic cleansing and genocide of the Rohingya ethnic minority to bloody coups, could not be suppressed due to technical and non-technical constraints. Civil society and the military organization are interrelated in Myanmar, and the country uses the strong relations between the two as best as it can for its internal interests to protect itself from foreign intervention. From a geographical point of view, Myanmar is located in the Southeast Asian region, with ASEAN as its regional organization. ASEAN is a unique regional organization whose member-states adopt a special principle called the principle of non-interference. According to the principle, all acts of interference from other countries are considered a violation and become an international crime when viewed from the Jus Cogens legal principle. This study then discusses the role of UNHCR as a facilitator to create peace by maintaining human rights. A qualitative method was then adopted to conduct the study, with data collection based on the news, journals, reports, and books. This study examines the concepts of democracy and human rights as an introduction to internal conflict in Myanmar and uses the concept of humanitarian diplomacy as an analysis of the role of UNHCR in Myanmar. Keywords: ASEAN, Democracy, Intervention, Humanity, Military Coup, UNHCR. Myanmar merupakan negara di Asia Tenggara dengan krisis kemanusiaan buruk yang ditandai dengan adanya isu konflik dan kemanusiaan. Kesewenangan militer terhadap warga sipil dimulai dari pembersihan etnis dan genosida etnis minoritas Rohingya, hingga kudeta militer yang tidak bisa diredam karena kendala teknis atau non-teknis. Keduanya saling berkaitan dan Myanmar memanfaatkannya sebaik mungkin untuk kepentingan internal untuk melindungi diri dari intervensi pihak asing. Ditinjau dari sisi geografis, Myanmar berada di wilayah Asia Tenggara dengan ASEAN sebagai organisasi internasional regional. ASEAN memiliki asas istimewa terhadap negara anggotanya untuk memberlakukan asas non-interference. Dengan begitu segala tindakan campur tangan dari negara lain dinilai sebagai sebuah pelanggaran dan menjadi sebuah tindakan kejahatan internasional apabila dipandang dari asas hukum Jus Cogens. Penelitian ini membahas tentang peran UNHCR sebagai fasilitator untuk menciptakan perdamaian dengan memelihara hak-hak atas kemanusiaan. Dengan berbasis pada berita, jurnal, laporan, dan buku sebagai hasil penjelasan dan telaahnya, sehingga tulisan ini bermetodekan kualitatif. Penelitian ini dikaji melalui konsep demokrasi dan HAM sebagai pengantar atas konflik internal di Myanmar, dan menggunakan konsep humanitarian diplomacy sebagai analisa atas peran UNHCR di negara Myanmar. Kata Kunci: ASEAN, Demokrasi, Intervensi, Kemanusiaan, Kudeta Militer, UNHCR.